2016
DOI: 10.1016/j.redox.2016.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2 mediates redox adaptations to exercise

Abstract: The primary aim of this review is to summarize the current literature on the effects of acute exercise and regular exercise on nuclear factor erythroid 2-related factor 2 (Nrf2) activity and downstream targets of Nrf2 signaling. Nrf2 (encoded in humans by the NFE2L2 gene) is the master regulator of antioxidant defenses, a transcription factor that regulates expression of more than 200 cytoprotective genes. Increasing evidence indicates that Nrf2 signaling plays a key role in how oxidative stress mediates the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
176
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(191 citation statements)
references
References 83 publications
3
176
0
1
Order By: Relevance
“…The fact that aerobic training reduces oxidative stress is not surprising: the training protocol used in the present study (Figure 1) was indeed demonstrated to increase aerobic capacity and to counteract protein and lipid oxidative modifications in skeletal muscles of heart failure-bearing animals [34]. In addition, many investigators have reported that exercise training boosts antioxidant defenses [33,34,[72][73][74] while decreasing lipid peroxidation [29] and oxidative modifications to proteins and RNA [55]. groups of mice (Table 1) and allowed to determine differences caused by adaptation of muscle to lack of CASQ1 (control CASQ1-null versus WT) and to training (control versus trained CASQ1-null).…”
Section: Protection From Oxidative Stress and Damagesupporting
confidence: 61%
“…The fact that aerobic training reduces oxidative stress is not surprising: the training protocol used in the present study (Figure 1) was indeed demonstrated to increase aerobic capacity and to counteract protein and lipid oxidative modifications in skeletal muscles of heart failure-bearing animals [34]. In addition, many investigators have reported that exercise training boosts antioxidant defenses [33,34,[72][73][74] while decreasing lipid peroxidation [29] and oxidative modifications to proteins and RNA [55]. groups of mice (Table 1) and allowed to determine differences caused by adaptation of muscle to lack of CASQ1 (control CASQ1-null versus WT) and to training (control versus trained CASQ1-null).…”
Section: Protection From Oxidative Stress and Damagesupporting
confidence: 61%
“…Nrf2 then binds to antioxidant response element (ARE) in the nucleus, mediating the transcription and expression of several key antioxidant genes, including NQO1, HO1 and GCLC [33][34][35][36]. Here, we showed that the mRNA expression levels of the Nrf2-dependent genes NQO1 (Fig.…”
Section: K6pc-5 Activates Nrf2 Signaling In Neuronal Cellsmentioning
confidence: 89%
“…4E), indicating Nrf2 protein stabilization. The latter is an essential step forNrf2 nuclear translocation and activation [33][34][35][36].…”
Section: K6pc-5 Activates Nrf2 Signaling In Neuronal Cellsmentioning
confidence: 99%
“…However, ubiquinol is a particular molecule endowed with both antioxidant properties but also critical for mitochondrial bioenergetics. Recent reports have highlighted that differently from other antioxidants, ubiquinol is able to promote Nrf2 translocation and hence to increase positive stimuli following physical exercise, while inhibiting the NFkB inflammatory pathway [65,[73][74][75].…”
Section: Discussionmentioning
confidence: 99%